Chromium-titanium dual-center catalyst and its preparation method and application
The chromium-titanium dual-center catalyst is used to achieve the production of polymers with bimodal molecular weight distribution in a single reactor, solving the problems of high equipment investment and energy consumption in the existing dual-reactor series process and improving the performance and ease of operation of the polymer.
Patent Information
- Application Number
- CN202111674337.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-31
- Publication Date
- 2025-09-26
- Estimated Expiration
- 2041-12-31
AI Technical Summary
When the existing dual-reactor series process is used to produce bimodal polyethylene, the equipment investment and energy consumption are high, the operation is difficult, and it is difficult to effectively control the molecular weight distribution of the polymer.
A chromium-titanium dual-center catalyst is used, which consists of a carrier, a chromium active component and a titanium active component. By being loaded on the carrier, the independent characteristics of the two metal centers are maintained, and it is used for the polymerization of olefins such as ethylene to regulate the molecular weight distribution of the polymer.
The production of polymers with bimodal molecular weight distribution is achieved in a single polymerization reactor, which reduces equipment investment and energy consumption, simplifies the operating process, and improves the long-term mechanical properties of the polymer.
Smart Images

Figure CN116410361B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polyethylene catalysts, and in particular to a chromium-titanium dual-center catalyst and a preparation method and application thereof. Background Art
[0002] Polyethylene is the most widely used plastic in the world, accounting for 39% of the most common thermoplastics and 62% of polyolefins. In the 1930s, Imperial Chemical Industries (ICI) pioneered the commercial application of low-density polyethylene (LDPE) through free radical polymerization. However, the product's weak mechanical properties limited its application in various fields. In the early 1950s, the inorganic chromium catalyst (Phillips catalyst) developed by Hogan and Banks of Phillips significantly improved the various properties of polyethylene, leading to its widespread application. Subsequently, in 1953, Karl Ziegler developed another catalyst with titanium as the active center, the Ziegler-Natta catalyst. The polyethylene produced by this catalyst, unlike that produced by the Phillips catalyst, possessed unique characteristics, meeting the needs of different applications. In the decades that followed, various high-performance polyethylenes were continuously developed and produced for applications in daily life, medicine, and the military. Currently, polyethylene is primarily classified into low-density polyethylene (LDPE), high-density polyethylene (HDPE), and linear low-density polyethylene (LLDPE). HDPE, due to its excellent mechanical properties and processing rheological characteristics, is widely used in packaging films, blow-molded containers, and extruded pipes, accounting for over 50% of the polyethylene market. Over the past 20-30 years, bimodal polyethylene (BPE) has rapidly developed as a high-performance polymer product, becoming the fastest-growing high-density polyethylene (HDPE) product. Currently, BPE is primarily produced via a two-reactor tandem process, where a catalyst synthesizes a higher molecular weight ethylene / α-olefin copolymer in one reactor, while a chain transfer agent, such as hydrogen, is introduced in a second reactor to synthesize a lower molecular weight ethylene homopolymer. This production process, requiring two reactors, requires high equipment investment and energy consumption, and is challenging to operate. Summary of the Invention
[0003] To address the above-mentioned issues, the present invention provides a chromium-titanium dual-site catalyst, its preparation method, and its application. The catalyst provided by the present invention maintains the independent properties of each active component and, when applied to olefin polymerization processes such as ethylene, can produce polymer products with bimodal molecular weights.
[0004] In order to achieve the above-mentioned object, the present invention provides a chromium-titanium dual-center catalyst, which includes a carrier and a chromium active component and a titanium active component supported on the carrier, wherein the weight of Cr in the chromium active component is 0.1-5wt% of the weight of the catalyst (i.e., the total weight of the chromium active component, the titanium active component and the carrier), and the weight of Ti in the titanium active component is 0.1-5wt% of the weight of the catalyst; the precursor of the chromium active component includes a chromocene compound, and the precursor of the titanium active component includes a titanocene compound.
[0005] The above-mentioned catalyst provided by the present invention is a supported catalyst. By loading the chromium active component and the titanium active component onto the carrier, the independent catalytic properties of the two metal centers can be maintained. When the catalyst is used for olefin polymerization, the structural properties of the polyethylene product can be effectively regulated through the active center to obtain a polymerization product with a wide molecular weight distribution and a bimodal distribution.
[0006] In the above catalyst, the structure of the chromocene compound can be shown as follows:
[0007] Cp1-Cr-Cp2,
[0008] Wherein, Cp1 and / or Cp2 may include one of cyclopentadienyl, indenyl and fluorenyl, that is, Cp1 and / or Cp2 may be one of the following structures:
[0009] In a specific embodiment, the structures of Cp1 and Cp2 may be the same or different without special limitation.
[0010] According to a specific embodiment of the present invention, the structure of the precursor of the chromium active component can be shown as follows:
[0011]
[0012] In the above catalyst, the structure of the titanocene compound can be shown as follows:
[0013]
[0014] Wherein, Cp may include one of cyclopentadienyl, indenyl and fluorenyl, and R1, R2 and R3 each include H or a hydrocarbon group with a carbon number of 1-8.
[0015] In a specific embodiment, the hydrocarbon group with a carbon number of 1-8 may include one or a combination of two or more of methyl, ethyl, propyl, isopropyl, butyl, tert-butyl, isobutyl, pentyl, isopentyl, hexyl, isohexyl, phenyl, benzyl, and benzyl.
[0016] According to a specific embodiment of the present invention, the precursor of the titanium active component may include the following structure:
[0017]
[0018] In the above catalyst, the carrier generally comprises a porous inorganic carrier. Specifically, the porous inorganic carrier may comprise one or a combination of two or more of silicon oxide, aluminum oxide, aluminosilicate, inorganic clay, titanium oxide, zirconium oxide, magnesium oxide, iron oxide, tin oxide, and zinc oxide. The inorganic clay may comprise montmorillonite, and the silicon oxide may comprise amorphous porous silica gel.
[0019] According to a specific embodiment of the present invention, the specific surface area of the porous inorganic carrier is generally 100-1000m 2 / g.
[0020] According to a specific embodiment of the present invention, the pore volume of the porous inorganic carrier is generally 0.3-5.0 cm 3 / g (i.e., the pore volume of the porous inorganic carrier is generally 0.3-5.0 cm 3 / g).
[0021] According to a specific embodiment of the present invention, the average pore diameter of the porous inorganic carrier is generally 5-50 nm.
[0022] In a specific embodiment of the present invention, an organometallic co-catalyst may be further added to the above catalyst as needed to activate the catalyst, that is, the catalyst further includes an organometallic co-catalyst. The organometallic co-catalyst may include one or a combination of two or more of an organoaluminum compound, an organolithium compound, an organoboron compound, and the like.
[0023] Specifically, the organoaluminum compound may include one or a combination of two or more of trialkylaluminum Al(R)3, alkylaluminoxane MAO, dialkylaluminum alkoxide Al(R)2OR, dialkylaluminum halide Al(R)2X, ethylaluminum sesquichloride, etc., wherein R is an alkyl group, which may be an alkyl group having 1 to 12 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-dodecyl, etc.; X is a halogen, such as fluorine, chlorine, bromine, and iodine, preferably chlorine. Preferably, the organoaluminum compound may include one or a combination of two or more of triethylaluminum, triisobutylaluminum, and alkylaluminoxane.
[0024] In a specific embodiment of the present invention, the molar ratio of the organometallic co-catalyst to Cr in the catalyst is 10-2000:1, preferably 50-400:1.
[0025] The present invention also provides a method for preparing the above-mentioned chromium-titanium dual-center catalyst, wherein the preparation method comprises: calcining a carrier, then impregnating the calcined carrier in a precursor of a chromium active component, a precursor of a titanium active component and an inert solvent, and drying to obtain the catalyst.
[0026] In the above preparation method, the calcination process can remove physical water and some hydroxyl groups on the surface of the carrier, exposing more active sites on the surface of the carrier that can combine with the active component precursor, thereby helping to improve the loading effect of chromium and titanium as active centers in the carrier.
[0027] In the above preparation method, a calcination temperature that is too low results in low removal of physical water and hydroxyl groups from the support surface, impairing the bonding between the active component precursor and the support; while a calcination temperature that is too high can destroy the microporous structure of the support. The present inventors have found that controlling the calcination temperature to 300-900°C, for example, 300-600°C, can improve the bonding between the active component precursor and the support.
[0028] In the above preparation method, the calcination time is generally controlled to be 1-10 hours, for example, 2-4 hours.
[0029] In the above preparation method, the calcination is generally carried out in a dry inert atmosphere, such as nitrogen or argon, to prevent air, water and other components from contaminating the catalyst.
[0030] In the above preparation method, the process of impregnating the calcined support with the precursor of the chromium active component and the precursor of the titanium active component can load the precursor of the chromium active component and the precursor of the titanium active component onto the support. In a specific embodiment of the present invention, the precursor of the chromium active component and the precursor of the titanium active component can be impregnated with the support in any order or simultaneously.
[0031] In the above preparation method, the impregnation temperature is generally controlled to be 20-180°C, for example, 45-120°C.
[0032] In the above preparation method, the immersion time is generally controlled to be 1-24 hours, for example, 4-12 hours.
[0033] According to a specific embodiment of the present invention, the inert solvent is used as a medium for the impregnation of the support. Specifically, the inert solvent may include one or a combination of two or more of benzene, toluene, and xylene. The inert solvent preferably includes toluene.
[0034] In the above preparation method, the drying process can remove the inert solvent in the system. Specifically, the drying temperature is generally controlled to be 60-150°C, for example, 80-130°C.
[0035] In the above preparation method, the drying time is generally controlled to be 2-24 hours, for example, 6-16 hours.
[0036] The present invention also provides the use of the chromium-titanium dual-site catalyst in olefin polymerization, such as ethylene polymerization.
[0037] In a specific embodiment of the present invention, the ethylene polymerization method may include polymerizing ethylene or ethylene and α-olefin as monomers to obtain an ethylene polymer; the catalyst used in the polymerization includes the above-mentioned chromium-titanium dual-site catalyst.
[0038] In a specific embodiment of the present invention, ethylene is polymerized as a monomer to obtain an ethylene homopolymer having a broad molecular weight distribution and generally a bimodal molecular weight distribution.
[0039] In a specific embodiment of the present invention, ethylene and α-olefins are polymerized as monomers to obtain a product having a generally broad molecular weight distribution, and the molecular weight of the product generally presents a bimodal distribution. In some specific embodiments, the product generally contains a relatively low molecular weight ethylene homopolymer product and a relatively high molecular weight ethylene and α-olefin copolymer product.
[0040] In a specific embodiment of the present invention, the carbon number of the α-olefin is generally 3-20. Specifically, the α-olefin may include one or a combination of two or more of propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-dodecene, 1-methyl-1-pentene, 4-methyl-1-hexene, etc. Preferably, the α-olefin may include one or a combination of two or more of 1-butene, 1-hexene and 1-octene.
[0041] In a specific embodiment of the present invention, during the above-mentioned ethylene polymerization process, monomers (ethylene or ethylene and α-olefin) are generally added into an organic solvent for polymerization.
[0042] During the ethylene polymerization process, the volume concentration of the monomer used for polymerization relative to the organic solvent is generally controlled to be greater than 0 vol% and less than or equal to 20 vol%, for example, greater than 0 vol% and less than or equal to 10 vol%. Specifically, when the monomer is ethylene, the volume concentration of ethylene relative to the organic solvent is generally controlled to be greater than 0 vol% and less than or equal to 20 vol%. When the monomers are ethylene and an α-olefin, the volume concentration of the α-olefin and ethylene relative to the organic solvent is generally controlled to be greater than 0 vol% and less than or equal to 20 vol%, for example, greater than 0 vol% and less than or equal to 10 vol%.
[0043] In a specific embodiment of the present invention, the organic solvent is generally an organic solvent that has been dehydrated and deoxygenated. Generally speaking, the organic solvent includes an alkane with a carbon number of 3-20. Specifically, the organic solvent can include one or a combination of two or more of propane, n-butane, isobutane, n-pentane, isopentane, neopentane, n-hexane, cyclohexane, n-heptane, n-octane, etc. Preferably, the organic solvent can include one or a combination of two or more of isobutane, isopentane, n-hexane, cyclohexane, n-heptane, etc.
[0044] In a specific embodiment of the present invention, during the ethylene polymerization process, a molecular weight regulator may be added during the polymerization reaction as needed. The molecular weight regulator may be hydrogen or the like.
[0045] In a specific embodiment of the present invention, the process for the polymerization of ethylene may include one or a combination of two or more of a gas phase polymerization process, a slurry polymerization process, a suspension polymerization process, a bulk polymerization process, a solution polymerization process, etc., and the above process can be implemented under conventional embodiments and polymerization conditions. The process for the polymerization of ethylene preferably includes a gas phase polymerization process and / or a slurry polymerization process. In some specific embodiments, the above ethylene polymerization process can be carried out in a single kettle.
[0046] According to a specific embodiment of the present invention, when ethylene polymerization is carried out using a slurry polymerization method, ethylene is generally first added to the reaction vessel, followed by the organic solvent and the monomers required for polymerization (when the chromium-titanium dual-site catalyst does not contain an organometallic co-catalyst, the organometallic co-catalyst is added simultaneously with the monomers), and then the chromium-titanium dual-site catalyst provided by the present invention is added to carry out polymerization to obtain a polymer product. In a specific embodiment, the polymerization process is typically carried out in a protective atmosphere (e.g., high-purity nitrogen); the polymerization process is terminated by adding a mixed solution of hydrochloric acid and ethanol.
[0047] According to a specific embodiment of the present invention, the specific process of ethylene polymerization using slurry polymerization includes: vacuum heating a reaction vessel (generally a reactor) to remove impurities, then repeatedly (three or more times) replacing the air in the reaction vessel with high-purity nitrogen, then introducing a small amount of ethylene for replacement, then filling ethylene into the reaction vessel until the ethylene reaches a slightly positive pressure (generally 0.1 MPa), adding an organic metal co-catalyst and a dehydrated and deoxygenated organic solvent, continuing to fill ethylene or ethylene and α-olefin (if molecular weight adjustment is required, hydrogen can be added at the same time), when the ethylene pressure reaches 1 MPa, adding a chromium-titanium dual-site catalyst to start the polymerization reaction (temperature is generally 35-100°C) to obtain an ethylene polymer. After the reaction reaches a certain level, a mixed solution of hydrochloric acid and ethanol is added to terminate the reaction. During the reaction, the instantaneous consumption of the monomer ethylene can be collected and recorded online. After the reaction is terminated, the polymer product can be washed, vacuum-dried, weighed, and then analyzed.
[0048] The beneficial effects of the present invention are:
[0049] 1. The two metal centers of the bimetallic center catalyst provided by the present invention can maintain independent catalytic properties. Therefore, the structural properties of polyethylene products can be effectively regulated through the active centers, thereby obtaining a polymer product with a wide molecular weight distribution and a bimodal distribution.
[0050] 2. The catalyst provided by the present invention can effectively regulate the molecular weight distribution of the polymer by hydrogen concentration and co-catalyst type based on the hydrogen sensitivity of the active center and the selectivity of the co-catalyst.
[0051] 3. The catalyst provided by the present invention can effectively insert the comonomer into the high molecular weight part based on the difference in copolymerization performance of the active center, which helps to improve the long-term mechanical properties of the bimodal polyethylene product.
[0052] 4. The catalyst provided by the present invention can synthesize polyethylene products with a bimodal molecular weight distribution in a single polymerization reactor. Compared with the existing two-reactor series process, this process has lower equipment investment and energy consumption and is simpler to operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 This is the molecular weight distribution result of the polymer prepared in Example 39.
[0054] Figure 2 This is the molecular weight distribution result of the polymer prepared in Example 40.
[0055] Figure 3 This is the molecular weight distribution result of the polymer prepared in Example 41.
[0056] Figure 4 This is the molecular weight distribution result of the polymer prepared in Example 42. DETAILED DESCRIPTION
[0057] In order to have a clearer understanding of the technical features, objectives and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be understood as limiting the scope of implementation of the present invention.
[0058] Unless otherwise specified, the reagents used in the examples and comparative examples can be purchased from the market.
[0059] Various polymer properties in Examples and Comparative Examples were measured according to the following methods:
[0060] 1. High-temperature gel chromatography (HT-GPC)
[0061] Weight-Average Molecular Weight and Molecular Weight Distribution by High-Temperature Gel Permeation Chromatography: This experiment used a PL-220 high-temperature gel permeation chromatograph (Polymer Laboratories) to determine polyethylene molecular weight and molecular weight distribution. Measurements were made at 160°C using 1,2,4-trichlorobenzene as the solvent. Data were processed using a universal calibration method using narrow-distribution polystyrene as a standard.
[0062] 2. 13C high temperature nuclear magnetic resonance spectroscopy (HT-13C NMR)
[0063] The short-chain branch content of the polymer was determined using high-temperature carbon nuclear magnetic resonance spectroscopy. This experiment used a Bruker Avance III 500 NMR spectrometer to determine the short-chain branch content of polyethylene. Deuterated p-dichlorobenzene was used as the solvent, and the measurement was performed at 110°C. The carbon signal on the polyethylene backbone (displacement at 30.00 ppm) was used as the internal standard to calculate the short-chain branch content.
[0064] 3. Polymerization activity: The ratio of the mass of the prepared polymerization product to the mass of the added catalyst is the polymerization activity.
[0065] The structures of the chromium active component precursors 1-3 and titanium active component precursor compounds 4-9 involved in the following examples and comparative examples are as follows. The above active component precursors are all commercially available:
[0066]
[0067]
[0068] Example 1 to Example 3:
[0069] Examples 1 to 3 provide chromium-titanium dual-site catalysts, the preparation method of which includes:
[0070] 1. 10g SiO2 carrier (specific surface area 500m 2 / g, pore volume 1.8cm 3 / g, pore size 21 nm) was placed in a fluidized bed for high-temperature calcination. The calcination process was carried out in a nitrogen atmosphere. The calcination temperatures of Examples 1 to 3 were 400°C, 600°C and 800°C, respectively (except for the calcination temperature, the other reaction conditions of Examples 1 to 3 were exactly the same), and the calcination time was 4 h. After the calcination, the heating was stopped and the SiO2 was allowed to cool naturally to room temperature. The calcined carrier was collected and stored in a nitrogen-protected environment.
[0071] 2. The calcined support was immersed in a toluene solution of a chromium active component precursor 1 and a titanium active component precursor 4 (the toluene solution used toluene as the sole solvent, as was the case with the toluene solutions in the following examples and comparative examples). The amount of the chromium active component precursor and the titanium active component precursor added was calculated based on the weight of Cr in the catalyst being 1 wt% of the total catalyst weight, and the amount of Ti added being 1 wt% relative to the total catalyst weight. After continuous stirring and impregnation at 80°C for 4 hours, the support was washed three times with 200 mL of toluene at room temperature, and then dried at 130°C for 4 hours in a nitrogen environment, to obtain chromium-titanium dual-site catalysts 1 to 3. The chromium-titanium dual-site catalysts were transferred and stored under nitrogen protection.
[0072] Example 4 to Example 6:
[0073] Examples 4 to 6 provide chromium-titanium dual-site catalysts, the preparation methods of which include:
[0074] 1. 10g SiO2 carrier (specific surface area 500m 2 / g, pore volume 1.8cm 3 / g, pore size 21nm) was placed in a fluidized bed for high-temperature calcination. The calcination process was carried out in a nitrogen atmosphere at a temperature of 600°C and a calcination time of 4h. After the calcination was completed, heating was stopped and the SiO2 was allowed to cool naturally to room temperature, and then collected and stored in a nitrogen-protected environment.
[0075] 2. The calcined support was immersed in a toluene solution of a precursor 1 of a chromium active component and a precursor 4 of a titanium active component, wherein the amount of the chromium active component precursor added in Examples 4 to 6 was calculated as 0.5 wt%, 2 wt%, and 4 wt% by weight of Cr relative to the total weight of the catalyst, respectively (except for the amount of Cr added, the other reaction conditions of Examples 4 to 6 were identical), and the amount of the titanium active component precursor calculated as 1 wt% by weight of Ti relative to the total weight of the catalyst; after continuous stirring and impregnation at 80°C for 4 hours, the support was washed with 200 mL of toluene three times at room temperature and then dried at 130°C for 4 hours in a nitrogen environment to obtain chromium-titanium dual-center catalysts 4 to 6. The chromium-titanium dual-center catalysts were transferred and stored under nitrogen protection.
[0076] Example 7 to Example 9:
[0077] Examples 7 to 9 provide chromium-titanium dual-site catalysts, the preparation methods of which include:
[0078] 10 g SiO2 carrier (specific surface area 500 m 2 / g, pore volume 1.8cm 3 / g, pore size 21nm) was placed in a fluidized bed for high-temperature calcination. The calcination process was carried out in a nitrogen atmosphere at a temperature of 600°C and a calcination time of 4h. After the calcination was completed, heating was stopped and the SiO2 was allowed to cool naturally to room temperature, and then collected and stored in a nitrogen-protected environment.
[0079] The calcined support was immersed in a toluene solution containing a certain concentration of a chromium active component precursor 1 and a titanium active component precursor 4, wherein the amount of the chromium active component precursor added was calculated based on the amount of Cr added relative to the total weight of the catalyst, and the amount of the titanium active component precursor added in Examples 7 to 9 was calculated based on the amount of Ti added relative to the total weight of the catalyst, respectively, at 0.5 wt%, 2 wt%, and 4 wt%. (Except for the amount of the titanium active component precursor added, the other reaction conditions of Examples 7 to 9 were exactly the same). After continuous stirring and impregnation at 80°C for 4 hours, the support was washed with 200 mL of toluene three times at room temperature, and then dried at 130°C for 4 hours. The drying process was carried out in a nitrogen environment to obtain chromium-titanium dual-center catalysts 7 to 9. The chromium-titanium dual-center catalysts were transferred and stored under nitrogen protection.
[0080] Example 10 to Example 11:
[0081] Examples 10 and 11 provide chromium-titanium dual-site catalysts, the preparation method of which includes:
[0082] 10 g SiO2 carrier (specific surface area 500 m2 / g, pore volume 1.8cm 3 / g, pore size 21nm) was placed in a fluidized bed for high-temperature calcination. The calcination process was carried out in a nitrogen atmosphere at a temperature of 600°C and a calcination time of 4h. After the calcination was completed, heating was stopped and the SiO2 was allowed to cool naturally to room temperature, and then collected and stored in a nitrogen-protected environment.
[0083] The calcined support was immersed in a toluene solution of a precursor of a chromium active component and a precursor of a titanium active component. The titanium active component precursor used in Examples 10 and 11 was titanium active component precursor 4, while the chromium active component precursors used in Examples 10 and 11 were chromium active component precursor 2 and chromium active component precursor 3, respectively (except for the type of chromium active component precursor, the other reaction conditions of Examples 10 and 11 were exactly the same); wherein, the amount of the chromium active component precursor and the titanium active component precursor added was calculated based on a total amount of Cr of 1 wt% relative to the total weight of the catalyst and an amount of Ti added of 1 wt% relative to the total weight of the catalyst; after continuous stirring and impregnation at 80°C for 4 hours, the support was washed with 200 mL of toluene three times at room temperature, and then dried at 130°C for 4 hours. The drying process was carried out in a nitrogen environment to obtain chromium-titanium dual-center catalysts 10 and 11. The chromium-titanium dual-center catalysts were transferred and stored under nitrogen protection.
[0084] Example 12 to Example 16:
[0085] Examples 12 to 16 provide chromium-titanium dual-site catalysts, the preparation methods of which include:
[0086] 10 g SiO2 carrier (specific surface area 500 m 2 / g, pore volume 1.8cm 3 / g, pore size 21nm) was placed in a fluidized bed for high-temperature calcination. The calcination process was carried out in a nitrogen atmosphere at a temperature of 600°C and a calcination time of 4h. After the calcination was completed, heating was stopped and the SiO2 was allowed to cool naturally to room temperature, and then collected and stored in a nitrogen-protected environment.
[0087] The calcined support was immersed in a toluene solution of a precursor of a chromium active component and a precursor of a titanium active component, wherein the chromium active component precursor used in Examples 12 to 16 was chromium active component precursor 1, and the titanium active component precursor used in Examples 12 to 16 was titanium active component precursor 5 to active component precursor 9, respectively (except for the type of titanium active component precursor, the other reaction conditions of Examples 12 to 16 were exactly the same); the amount of the chromium active component precursor and the titanium active component precursor added was calculated based on 1 wt% of Cr and 1 wt% of Ti relative to the total weight of the catalyst; after continuous stirring and impregnation at 80°C for 4 hours, the support was washed with 200 mL of toluene three times at room temperature, and then dried at 130°C for 4 hours. The drying process was carried out in a nitrogen environment to obtain chromium-titanium dual-center catalysts 12 to 16. The chromium-titanium dual-center catalysts were transferred and stored under nitrogen protection.
[0088] Example 17
[0089] Example 17 provides a chromium-titanium dual-site catalyst, the preparation method of which comprises:
[0090] 10 g SiO2 carrier (specific surface area 500 m 2 / g, pore volume 1.8cm 3 / g, pore size 21nm) was placed in a fluidized bed for high-temperature calcination. The calcination process was carried out in a nitrogen atmosphere at a temperature of 600°C and a calcination time of 4h. After the calcination was completed, heating was stopped and the SiO2 was allowed to cool naturally to room temperature, and then collected and stored in a nitrogen-protected environment.
[0091] The calcined support was immersed in a toluene solution of a precursor 1 of a chromium active component, where the amount of the precursor was calculated as 1 wt% by weight of Cr relative to the total weight of the catalyst. After continuous stirring and reacting at 80°C for 4 hours, a toluene solution of a precursor 4 of a titanium active component was added, where the amount of the precursor was calculated as 1 wt% by weight of Ti relative to the total weight of the catalyst. After continuous stirring and impregnation at 80°C for 4 hours, the support was washed with 200 mL of toluene three times at room temperature, and then dried at 130°C for 4 hours in a nitrogen environment to obtain a chromium-titanium dual-center catalyst 17. The chromium-titanium dual-center catalyst was transferred and stored under nitrogen protection.
[0092] Example 18
[0093] Example 18 provides a chromium-titanium dual-site catalyst, the preparation method of which comprises:
[0094] 10 g SiO2 carrier (specific surface area 500 m 2 / g, pore volume 1.8cm3 / g, pore size 21nm) was placed in a fluidized bed for high-temperature calcination. The calcination process was carried out in a nitrogen atmosphere at a temperature of 600°C and a calcination time of 4h. After the calcination was completed, heating was stopped and the SiO2 was allowed to cool naturally to room temperature, and then collected and stored in a nitrogen-protected environment.
[0095] The calcined support was immersed in a toluene solution of a titanium active component precursor 1, where the amount of the titanium active component precursor added was calculated as 1 wt% by weight of Ti relative to the total weight of the catalyst. After continuous stirring and impregnation at 80°C for 4 hours, a toluene solution of a chromium active component precursor 4 was added, where the amount of the chromium active component precursor added was calculated as 1 wt% by weight of Cr relative to the total weight of the catalyst. After continuous stirring and reaction at 80°C for 4 hours, the support was washed with 200 mL of toluene three times at room temperature, and then dried at 130°C for 4 hours in a nitrogen environment to obtain a chromium-titanium dual-center catalyst 18. The chromium-titanium dual-center catalyst was transferred and stored under nitrogen protection.
[0096] Example 19
[0097] Example 19 provides a chromium-titanium dual-site catalyst, the preparation method of which comprises:
[0098] 10 g SiO2 carrier (specific surface area 500 m 2 / g, pore volume 1.8cm 3 / g, pore size 21nm) was placed in a fluidized bed for high-temperature calcination. The calcination process was carried out in a nitrogen atmosphere at a temperature of 600°C and a calcination time of 4h. After the calcination was completed, heating was stopped and the SiO2 was allowed to cool naturally to room temperature, and then collected and stored in a nitrogen-protected environment.
[0099] The calcined support was immersed in a toluene solution of a precursor 1 of a chromium active component and a precursor 4 of a titanium active component. The added amounts of the precursors of the chromium active component and the titanium active component were calculated based on the weight of Cr being 1 wt% relative to the total weight of the catalyst and the weight of Ti being 1 wt% relative to the total weight of the catalyst. After continuous stirring and impregnation at 80°C for 4 hours, the support was washed with 200 mL of toluene three times at room temperature. The support was then cooled to 45°C and a toluene solution of methylaluminoxane was added to pre-activate the catalyst. The amount of methylaluminoxane added was calculated based on an Al / Cr molar ratio of 100. The activation process was carried out under stirring for 1 hour, and then the support was heated to 130°C and dried for 4 hours. The drying process was carried out in a nitrogen environment to obtain a chromium-titanium dual-center catalyst 19. The chromium-titanium dual-center catalyst was transferred and stored under nitrogen protection.
[0100] Comparative Example 1
[0101] This comparative example provides a catalyst, the preparation method of which comprises:
[0102] 10 g SiO2 carrier (specific surface area 500 m 2 / g, pore volume 1.8cm 3 / g, pore size 21nm) was placed in a fluidized bed for high-temperature calcination. The calcination process was carried out in a nitrogen atmosphere at a temperature of 600°C and a calcination time of 4h. After the calcination was completed, heating was stopped and the SiO2 was allowed to cool naturally to room temperature, and then collected and stored in a nitrogen-protected environment.
[0103] The calcined support was immersed in a toluene solution of a precursor 1 of a chromium active component, where the amount of the precursor of the chromium active component added was calculated to be 1 wt% by weight of Cr relative to the total weight of the catalyst. After continuous stirring and immersion at 80°C for 4 hours, the support was washed with 200 mL of toluene three times at room temperature and then dried at 130°C for 4 hours in a nitrogen environment to obtain a catalyst, which was then transferred and stored under nitrogen protection.
[0104] Comparative Example 2
[0105] This comparative example provides a catalyst, the preparation method of which comprises:
[0106] 10 g SiO2 carrier (specific surface area 500 m 2 / g, pore volume 1.8cm 3 / g, pore size 21nm) was placed in a fluidized bed for high-temperature calcination. The calcination process was carried out in a nitrogen atmosphere at a temperature of 600°C and a calcination time of 4h. After the calcination was completed, heating was stopped and the SiO2 was allowed to cool naturally to room temperature, and then collected and stored in a nitrogen-protected environment.
[0107] The calcined support was immersed in a toluene solution of a precursor 4 of a titanium active component, where the amount of the precursor of the titanium active component added was calculated to be 1 wt% based on the weight of Ti relative to the total weight of the catalyst; after continuous stirring and impregnation at 80°C for 4 hours, the support was washed three times with 200 mL of toluene at room temperature, and then dried at 130°C for 4 hours. The drying process was carried out in a nitrogen environment to obtain a catalyst, which was transferred and stored under nitrogen protection.
[0108] Example 20 to Example 38
[0109] Examples 20 to 38 provide ethylene polymerization methods using the chromium-titanium dual-site catalysts prepared in Examples 1 to 18. The polymerization methods comprise:
[0110] 100 mg of the catalyst was mixed with 10 ml of purified (dehydrated and deoxygenated) toluene to form a catalyst suspension. Examples 20 to 37 respectively used the chromium-titanium dual-site catalysts prepared in Examples 1 to 18, and Example 38 used the chromium-titanium dual-site catalyst prepared in Example 18.
[0111] A 2L stainless steel high-pressure polymerization reactor was vacuum heated to remove impurities and evacuated three times with high-purity nitrogen. A trace amount of refined hydrogen was then introduced into the reactor to 0.1 MPa. Next, 900 mL of refined toluene solvent was added. For Examples 20 to 38, methylaluminoxane (MAO) with an Al / Cr molar ratio of 100 was added as a cocatalyst, while for Example 38, 0.3 mmol of triisobutylaluminum was added as an impurity remover (i.e., only methylaluminoxane was added without triisobutylaluminum in Examples 20 to 37; both methylaluminoxane and triisobutylaluminum were added in Example 38). 100 mL of dehydrated, deoxygenated, and purified toluene solvent was then added. Ethylene was added to adjust the reactor pressure to 1 MPa. After the reactor temperature was stabilized at 80°C, the catalyst suspension was hydraulically injected into the reactor using high-pressure nitrogen to initiate the reaction. During the reaction, the instantaneous ethylene monomer consumption was collected online and recorded by a computer. After the polymerization reaction was carried out for 1 hour, a mixed solution of hydrochloric acid and ethanol was added to terminate the reaction, and the polymer product was filtered and dried in a vacuum drying oven at 60° C. for 4 hours to obtain the polymer product, which was then weighed and analyzed.
[0112] Example 39
[0113] Example 39 provides an ethylene polymerization method using the chromium-titanium dual-site catalyst prepared in Example 2, the polymerization method comprising:
[0114] 100 mg of the catalyst prepared in Example 2 was mixed with 10 ml of purified toluene to form a catalyst suspension.
[0115] A 2L stainless steel high-pressure polymerization reactor was vacuum heated to remove impurities, and evacuated three times with high-purity nitrogen. Finally, a trace amount of refined hydrogen was added to the reactor, wherein the amount of hydrogen added was 0.1MPa. Then, 900ml of refined toluene solvent and methylaluminoxane (MAO) as a co-catalyst were added to the reactor in turn. The amount of methylaluminoxane added was calculated according to Al / Cr=100 (molar ratio), and then 100mL of dehydrated and deoxygenated refined toluene solvent was added. Ethylene was added to adjust the ethylene pressure in the reactor to 1MPa. After the temperature in the reactor was constant at 80°C, the catalyst suspension was hydraulically injected into the polymerization reactor using high-pressure nitrogen to start the reaction. During the reaction, the instantaneous consumption of monomer ethylene was collected online and recorded by a computer. After the polymerization reaction was carried out for 1h, a mixed solution of hydrochloric acid and ethanol was added to terminate the reaction. The polymerization product was filtered and dried at 60°C in a vacuum drying oven for 4h. The polymerization product was weighed and analyzed. The molecular weight distribution of the obtained polymer is as follows Figure 1 shown.
[0116] Example 40
[0117] Example 40 provides an ethylene polymerization method using the chromium-titanium dual-site catalyst prepared in Example 2, the polymerization method comprising:
[0118] 100 mg of the catalyst prepared in Example 2 was mixed with 10 ml of purified toluene to form a catalyst suspension.
[0119] The 2L stainless steel high-pressure polymerization reactor was vacuum heated to remove impurities, and was evacuated three times with high-purity nitrogen. Finally, a trace amount of refined hydrogen was added to the reactor to 0.1MPa. Then, 900ml of refined toluene solvent and methylaluminoxane (MAO) as a co-catalyst were added to the reactor in sequence, wherein the amount of co-catalyst added was calculated based on the Al / Cr molar ratio of 200, and then 100mL of dehydrated and deoxygenated refined toluene solvent was added. Ethylene was added to adjust the ethylene pressure in the reactor to 1MPa. After the temperature in the reactor was constant at 80°C, the catalyst suspension was hydraulically injected into the polymerization reactor using high-pressure nitrogen to start the reaction. During the reaction, the instantaneous consumption of monomer ethylene was collected online and recorded by a computer. After the polymerization reaction was carried out for 1h, a mixed solution of hydrochloric acid and ethanol was added to terminate the reaction. After filtration, the obtained polymer was dried at 60°C in a vacuum drying oven for 4h to obtain a polymerization product, which was weighed and analyzed. The molecular weight distribution of the obtained polymer is as follows Figure 2 shown.
[0120] Example 41
[0121] Example 41 provides an ethylene polymerization method using the chromium-titanium dual-site catalyst prepared in Example 2, the polymerization method comprising:
[0122] 100 mg of the catalyst prepared in Example 2 was mixed with 10 ml of purified toluene to form a catalyst suspension.
[0123] A 2L stainless steel high-pressure polymerization reactor was vacuum heated to remove impurities, and evacuated three times with high-purity nitrogen. Finally, a trace amount of refined hydrogen was added to the reactor to 0.1MPa. Then, 900ml of refined toluene solvent and triethylaluminum as a co-catalyst were added to the reactor in turn. The amount of co-catalyst added was calculated based on the Al / Cr molar ratio of 100, and then 100mL of dehydrated and deoxygenated refined toluene solvent was added. Ethylene was added to adjust the ethylene pressure in the reactor to 1MPa. After the temperature in the reactor was constant at 80°C, the catalyst suspension was hydraulically injected into the polymerization reactor using high-pressure nitrogen to start the reaction. During the reaction, the instantaneous consumption of monomer ethylene was collected online and recorded by a computer. After the polymerization reaction was carried out for 1h, a mixed solution of hydrochloric acid and ethanol was added to terminate the reaction. After filtration, the obtained polymer was dried at 60°C in a vacuum drying oven for 4h to obtain a polymerization product, which was weighed and analyzed. The molecular weight distribution of the obtained polymer is as follows Figure 3 shown.
[0124] Example 42
[0125] Example 42 provides an ethylene polymerization method using the chromium-titanium dual-site catalyst prepared in Example 2, the polymerization method comprising:
[0126] 100 mg of the catalyst prepared in Example 2 was mixed with 10 ml of purified toluene to form a catalyst suspension.
[0127] A 2L stainless steel high-pressure polymerization reactor was vacuum heated to remove impurities, and evacuated three times with high-purity nitrogen. Finally, a trace amount of refined hydrogen was added to the reactor to 0.1MPa. Then, 900ml of refined toluene solvent and a certain amount of 1-hexene comonomer were added to the reactor in turn, of which the amount of 1-hexene added was 10mL. Subsequently, methylaluminoxane (MAO) with an amount of Al / Cr=100 (molar ratio) was added as a co-catalyst, and then 100mL of dehydrated and deoxygenated refined toluene solvent was added. Ethylene was added to adjust the ethylene pressure in the reactor to 1MPa. After the temperature in the reactor was constant at 80°C, the catalyst suspension was hydraulically injected into the polymerization reactor using high-pressure nitrogen to start the reaction. During the reaction, the instantaneous consumption of monomer ethylene was collected online and recorded by a computer. After the polymerization reaction was carried out for 1h, a mixed solution of hydrochloric acid and ethanol was added to terminate the reaction. After filtration, the obtained polymer was dried at 60°C in a vacuum drying oven for 4h to obtain a polymerization product, which was weighed and analyzed. The molecular weight distribution of the obtained polymer is as follows Figure 4 shown.
[0128] Comparative Example 3 to Comparative Example 4
[0129] Comparative Examples 3 and 4 provide ethylene polymerization methods using the chromium-titanium dual-site catalysts prepared in Comparative Examples 1 and 2. The polymerization methods comprise:
[0130] 100 mg of catalyst was mixed with 10 ml of purified toluene to form a catalyst suspension. Comparative Example 3 used the chromium-titanium dual-center catalyst prepared in Comparative Example 1, and Comparative Example 4 used the chromium-titanium dual-center catalyst prepared in Comparative Example 2.
[0131] A 2L stainless steel high-pressure polymerization reactor was vacuum heated to remove impurities and evacuated three times with high-purity nitrogen. A trace amount of refined hydrogen was then added to the reactor to a pressure of 0.1 MPa. 900 ml of refined toluene solvent and methylaluminoxane (MAO) as a co-catalyst were then added to the reactor in sequence. The amount of methylaluminoxane added was calculated according to an Al / Cr molar ratio of 100. 100 mL of dehydrated and deoxygenated refined toluene solvent was then added. Ethylene was added to adjust the ethylene pressure in the reactor to 1 MPa. After the temperature in the reactor was constant at 80°C, the catalyst suspension was hydraulically pressed into the polymerization reactor using high-pressure nitrogen to initiate the reaction. During the reaction, the instantaneous consumption of monomer ethylene was collected online and recorded by a computer. After the polymerization reaction was carried out for 1 hour, a mixed solution of hydrochloric acid and ethanol was added to terminate the reaction. After filtration, the resulting polymer was dried in a vacuum drying oven at 60°C for 4 hours, weighed, and analyzed.
[0132] Comparative Example 5 to Comparative Example 6
[0133] Comparative Examples 5 and 6 provide ethylene polymerization methods using the chromium-titanium dual-site catalysts prepared in Comparative Examples 1 and 2, the polymerization methods comprising:
[0134] 100 mg of the catalyst was mixed with 10 ml of purified toluene to form a catalyst suspension. Comparative Example 5 used the chromium-titanium dual-center catalyst prepared in Comparative Example 1, and Comparative Example 6 used the chromium-titanium dual-center catalyst prepared in Comparative Example 2.
[0135] A 2L stainless steel high-pressure polymerization reactor was vacuum heated to remove impurities and evacuated three times with high-purity nitrogen. Then, 0.1MPa of refined hydrogen was added to the reactor. Then, 900ml of refined toluene solvent and methylaluminoxane (MAO) as a co-catalyst were added to the reactor in sequence. The amount of methylaluminoxane was calculated according to Al / Cr = 100 (molar ratio). Then, 100mL of dehydrated and deoxygenated refined toluene solvent was added. Ethylene was added to adjust the ethylene pressure in the reactor to 1MPa. After the temperature in the reactor was constant at 80°C, the catalyst suspension was hydraulically injected into the polymerization reactor using high-pressure nitrogen to initiate the reaction. During the reaction, the instantaneous consumption of monomer ethylene was collected online and recorded by a computer. After the polymerization reaction was carried out for 1 hour, a mixed solution of hydrochloric acid and ethanol was added to terminate the reaction. After filtration, the resulting polymer was dried in a vacuum drying oven at 60°C for 4 hours, weighed, and analyzed.
[0136] Comparative Examples 7 to 8
[0137] Comparative Examples 7 and 8 provide ethylene polymerization methods using the chromium-titanium dual-site catalysts prepared in Comparative Examples 1 and 2, the polymerization methods comprising:
[0138] 100 mg of the catalyst was mixed with 10 ml of purified toluene to form a catalyst suspension. Comparative Example 7 used the chromium-titanium dual-center catalyst prepared in Comparative Example 1, and Comparative Example 8 used the chromium-titanium dual-center catalyst prepared in Comparative Example 2.
[0139] A 2L stainless steel high-pressure polymerization reactor was vacuum heated to remove impurities and evacuated three times with high-purity nitrogen. A trace amount of purified hydrogen was then added to the reactor to a pressure of 0.1 MPa. 900 mL of purified toluene solvent and 30 mL of 1-hexene comonomer were then added, followed by the addition of methylaluminoxane (MAO) with an Al / Cr ratio of 100 as a cocatalyst. 100 mL of dehydrated and deoxygenated purified toluene solvent was then added. Ethylene was added to adjust the pressure in the reactor to 1 MPa. After the reactor temperature remained constant at 80°C, the catalyst suspension was hydraulically injected into the reactor using high-pressure nitrogen to initiate the reaction. During the reaction, the instantaneous ethylene monomer consumption was collected online and recorded by a computer. After one hour of polymerization, a mixed solution of hydrochloric acid and ethanol was added to terminate the reaction. After filtration, the resulting polymer was dried in a vacuum drying oven at 60°C for 4 hours, weighed, and analyzed.
[0140] The analysis results of the polymerization products of Examples 20 to 42 and Comparative Examples 3 to 8 are summarized in Table 1.
[0141] Table 1
[0142]
[0143]
[0144] As can be seen from Table 1, compared with the single-active-site catalyst, the catalyst with dual active centers provided by the present invention has higher polymerization activity, and the molecular weight distribution of the obtained polymerization product is wider.
[0145] The present invention may be summarized in other specific forms that do not violate the spirit or main features of the present invention. The above embodiments of the present invention can only be regarded as an illustration of the present invention rather than a limitation. Any slight modifications, equivalent changes and modifications made to the above embodiments based on the essential technology of the present invention are within the scope of the technical solution of the present invention.
Claims
1. A chromium-titanium dual-site catalyst comprising a carrier and a chromium active component and a titanium active component supported on the carrier, wherein the weight of Cr in the chromium active component is 0.1-5 wt% of the weight of the catalyst, and the weight of Ti in the titanium active component is 0.1-5 wt% of the weight of the catalyst; the precursor of the chromium active component comprises a chromocene compound, and the precursor of the titanium active component comprises a titanocene compound; The structure of the titanocene compound is shown below: in, Cp includes one of cyclopentadienyl, indenyl and fluorenyl, and R1, R2 and R3 each include H or a hydrocarbon group having 1 to 8 carbon atoms; The structure of the chromocene compound is shown below: Cp1-Cr-Cp2, Wherein, Cp1 and / or Cp2 include one of cyclopentadienyl, indenyl and fluorenyl.
2. The catalyst according to claim 1, wherein In the structure of the titanocene compound, the hydrocarbon group with a carbon number of 1-8 includes one or a combination of two or more of methyl, ethyl, propyl, isopropyl, butyl, tert-butyl, isobutyl, pentyl, isopentyl, hexyl, isohexyl, phenyl, benzyl, and benzyl.
3. The catalyst according to claim 1, wherein The precursor of the titanium active component includes one of the following structures:
4. The catalyst according to claim 1, wherein The structure of the precursor of the chromium active component includes one of the following structures:
5. The catalyst according to claim 1, wherein The support includes a porous inorganic support. The catalyst according to claim 1 , wherein The porous inorganic carrier includes one or a combination of two or more of silicon oxide, aluminum oxide, aluminosilicate, inorganic clay, titanium oxide, zirconium oxide, magnesium oxide, iron oxide, tin oxide, and zinc oxide.
7. The catalyst according to claim 6, wherein The inorganic clay includes montmorillonite, and the silicon oxide includes amorphous porous silica gel.
8. The catalyst according to claim 5, wherein The specific surface area of the porous inorganic carrier is 100-1000m 2 / g, pore volume of 0.3-5.0cm 3 / g, and the average pore size is 5-50nm.
9. The catalyst according to any one of claims 1 to 8, wherein The catalyst further comprises an organometallic co-catalyst.
10. The catalyst according to claim 9, wherein The organometallic co-catalyst includes one or a combination of two or more of an organoaluminum compound, an organolithium compound, and an organoboron compound. The catalyst according to claim 10 , wherein The organoaluminum compound includes one or a combination of two or more of trialkylaluminum Al(R)3, alkylaluminoxane, dialkyl alkoxyaluminum Al(R)2OR, dialkylaluminum halide Al(R)2X, and ethyl sesquialuminum chloride, wherein X is a halogen and R is an alkyl.
12. The catalyst according to claim 11, wherein R is an alkyl group having 1 to 12 carbon atoms.
13. The catalyst according to claim 11, wherein R is one or a combination of two or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, and n-dodecyl.
14. The catalyst according to claim 11, wherein The organic aluminum compound includes one or a combination of two or more of triethylaluminum, triisobutylaluminum and alkylaluminoxane.
15. The catalyst according to claim 9, wherein The molar ratio of the organic metal co-catalyst to Cr in the catalyst is 10-2000:
1.
16. The catalyst according to claim 15, wherein The molar ratio of the organic metal co-catalyst to Cr in the catalyst is 50-400:
1.
17. The method for preparing a chromium-titanium dual-site catalyst according to any one of claims 1 to 16, wherein: The preparation method comprises the following steps: calcining a carrier, then immersing the calcined carrier in a precursor of a chromium active component, a precursor of a titanium active component and an inert solvent, and drying to obtain the catalyst.
18. The preparation method according to claim 17, wherein The calcination temperature is 300-900°C; The calcination time is 1-10 hours.
19. The preparation method according to claim 18, wherein The calcination temperature is 300-600°C.
20. The preparation method according to claim 18, wherein The calcination time is 2-4 hours.
21. The preparation method according to claim 18, wherein The calcination is carried out in a dry inert atmosphere.
22. The preparation method according to claim 17, wherein The immersion temperature is 20-180° C.; the immersion time is 1-24 hours.
23. The preparation method according to claim 22, wherein The immersion temperature is 45-120°C.
24. The preparation method according to claim 22, wherein The immersion time is 4-12 hours.
25. The preparation method according to claim 17, wherein The inert solvent includes one or a combination of two or more of benzene, toluene and xylene.
26. The preparation method according to claim 17, wherein The inert solvent includes toluene.
27. Use of the chromium-titanium dual-site catalyst according to any one of claims 1 to 16 in olefin polymerization.
28. The use according to claim 27, wherein: The olefin polymerization includes ethylene polymerization, and the ethylene polymerization method includes polymerizing ethylene or ethylene and α-olefin as monomers to obtain ethylene polymer; the catalyst used in the polymerization includes the chromium-titanium dual-center catalyst according to any one of claims 1-14.
29. The use according to claim 28, wherein The α-olefin has a carbon number of 3-20.
30. The use according to claim 29, wherein The α-olefins include one or a combination of two or more of propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-dodecene, 1-methyl-1-pentene, and 4-methyl-1-hexene.
31. The use according to claim 29, wherein: The α-olefin includes one or a combination of two or more of 1-butene, 1-hexene and 1-octene.
32. The use according to claim 28, wherein In the above ethylene polymerization process, ethylene or ethylene and α-olefin are added as monomers into an organic solvent for polymerization.
33. The use according to claim 32, wherein: The volume concentration of the monomer relative to the organic solvent is greater than 0 vol % and less than or equal to 20 vol %.
34. The use according to claim 32, wherein: The volume concentration of the monomer relative to the organic solvent is greater than 0 vol % and less than or equal to 10 vol %.
35. The use according to claim 33, wherein The organic solvent includes an alkane having a carbon number of 3 to 20.
36. The use according to claim 35, wherein The organic solvent includes one or a combination of two or more of propane, n-butane, isobutane, n-pentane, isopentane, neopentane, n-hexane, cyclohexane, n-heptane and n-octane.
37. The use according to claim 36, wherein The organic solvent includes one or a combination of two or more of isobutane, isopentane, n-hexane, cyclohexane and n-heptane.
38. The use according to claim 28, wherein The ethylene polymerization process includes one or a combination of two or more of a gas phase polymerization process, a slurry polymerization process, a suspension polymerization process, a bulk polymerization process, and a solution polymerization process.
39. The use according to claim 28, wherein The ethylene polymerization process includes a gas phase polymerization process and / or a slurry polymerization process.
Citation Information
Patent Citations
Metallocene and Half Sandwich Dual Catalyst Systems for Producing Broad Molecular Weight Distribution Polymers
US20140088274A1
Preparation of modified and activated chromocene catalysts for ethylene polymerization
US4101445A